Функціональні, біометричні та біомеханічні зміни параметрів ока при міопії у дітей: особливості лікування та оптичної корекції - Цибульська, Таміла Євгенівна; Tsybulska, T. E. (Запорізький державний медичний університет, 2020)
Дисертація присвячена вирішенню актуальної науково-прикладної проблеми сучасної офтальмології – підвищенню ефективності лікування міопії у дітей з застосуванням патогенетично обґрунтованої корекції порушень, виявлених на підставі комплексного дослідження функціональних показників, біометричних, біомеханічних параметрів ока та біохімічних особливостей метаболізму сполучної тканини з наступною оптичною корекцією. Встановлено, що зміни в функціональних, біометричних, біомеханічних параметрах зорового аналізатора, біохімічних показниках метаболізму сполучної тканини представляють собою єдиний комплекс патогенетичних змін при розвитку і прогресуванні набутої міопії у дітей. Визначено кількісні офтальмологічні критерії зорового аналізатора, які дозволяють проводити дискримінацію при набутій міопії між наявністю синдрому недиференційованої дисплазії сполучної тканини та його відсутністю. Математичним моделюванням отримана сукупність предикторов, що визначають розвиток і прогресування набутої міопії у дітей, до яких відносяться індивідуальні біометричні, біомеханічні параметри ока, стан акомодації, анамнестичні дані, стигми сполучнотканинної дисплазії та встановлені їх кількісні показники. Клініко-біохімічними дослідженнями виявлені патологічні особливості в патогенезі набутої міопії, які полягають в зниженні рівня магнію, кальцію, підвищенні гідроксипроліну у добовій сечі, встановлено взаємозв'язки між змінами даних біохімічних показників з параметрами зорового аналізатора при прогресуючої набутій міопії. Доведено, що прогресуюча міопія вимагає оцінки загального стану організму дитини. Обґрунтовано необхідність повної оптичної корекції міопічної рефракції, переваги ортокератологічної оптичної корекції, а також необхідність застосування місцевої та загальної метаболічної терапії в комплексному лікуванні прогресуючої міопії у дітей. The dissertation is dedicated to solving the urgent scientific and applied problem of modern ophthalmology - improving the effectiveness of treatment and optical correction in children with acquired myopia based on a comprehensive study of functional, biometric, biomechanical changes in eye parameters and biochemical features of connective tissue metabolism with subsequent pathogenetically substantiated correction of the revealed disorders. It was found that the progressive course of myopia was observed 3 times more often among children with the presence of undifferentiated connective tissue dysplasia syndrome: 67.7 ± 8.4 % versus 22.5 ± 3.2 % (p <0.05). Assessment of the influence of phenotypic features of connective tissue dysplasia on the progression of myopia showed that in children 7-11 years the main risk factors were: degree of dysplasia (HV = 7.5; 95 % CI = 3.1-9.8, p <0.05), hypermobility of the joints (HV 5.5; 95 % CI = 2.1-9.7, p < 0.05), asthenic type of constitution (HV = 4.9; 95 % CI = 2.1-11.8, p <0.05), venous mesh on the skin (HF 4.8; 95 % CI = 2, 9-20.7, p <0.05), flatfoot (HV = 4.1; 95 % CI = 1.7-9.5, p <0.05). Among the risk factors for the progression of myopia in children 12-15 years old, the most informative were presence of moderate or severe connective tissue dysplasia in children (HV = 7.9; 95 % CI = 3.2-19.3, p <0.05) hypermobility of the joints (HV = 7.1; 95 % CI = 2.7-13.6, p <0.05), as well as the asthenic constitution type (HV = 7.1; 95 % CI = 3.2-15.7 ), heart valve prolapse and other small heart abnormalities (HV = 6.9; 95 % CI = 3.1 -15.3, p <0.05), postural abnormalities, scoliosis (HV = 5.6; 95 % CI = 2.5-12.4, p <0.05) and skin hyperelasticity (HV = 5.3; 95% CI = 2.3-12.5, p <0.05). We determined the features of visual analyzer condition in children with progressive acquired myopia associated with connective tissue dysplasia syndrome, which are in violation of the accommodative function by an average of 3.4 times, reduction of the corneal refractive power by an average of 4.6 % (p<0.05), corneal hysteresis by 7.5 % (p <0.05), increase in radius curvature of 5.3 % (p <0.05), and corneal diameter of 7.2 % (p <0.05), increase of the anterior chamber depth by 5.2% (p<0.05), sagittal length of vitreous body by 9.2 % (p <0.05) and axial eye length by 4.2 % (p <0.05), a decrease in the average thickness of the layer of peripapillary nerve fibers by 11% due to the upper by 7.0 %, lower by 8.5 %, and nasal sector by 18.2 % (p <0.05), and also increase in retinal thickness in the fovea by 6.7% (p <0.05), compared with patients with myopia without connective tissue dysplasia.
Functional, biometric and biomechanical changes in eye parameters during myopia in children: features of treatment and optical correction
Keywords: міопія; синдром недиференційованої дисплазії сполучної тканини; прогнозування; лікування; оптична корекція; myopia; syndrome of undifferentiated connective tissue dysplasia; prognosis; treatment; optical correction